2013
DOI: 10.1177/0886260513488696
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse and Criminal Behavior

Abstract: This article draws on general strain theory (GST) to develop and test a model of the childhood abuse-crime relationship. Using data from the National Longitudinal Study of Adolescent Health (Add Health),(1) we find that early childhood physical and sexual abuse are robust predictors of offending in adolescence, for the full sample and in equations disaggregated by gender. GST is partially supported in that the effects of childhood physical abuse on offending for both females and males are mediated by an index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 48 publications
1
23
0
1
Order By: Relevance
“…This third type of strain can include a wide range of stressful life events, such as criminal victimization or negative relationships with parents, teachers, or peers (Agnew & White, 1992). GST recognizes a number of victimization experiences that are likely to cause delinquency and have been neglected by other theories of crime (Agnew, 2002), and empirical tests of GST provide strong support for the victimization-delinquency relationship (Agnew, 1985(Agnew, , 2002Agnew & White, 1992;Jackson, Hanson, Amstadter, Saunders, & Kilpatrick, 2013;Mersky, Topitzes, & Reynolds, 2012;Moon, Morash, McCluskey, & Hwang, 2009;Sigfusdottir, Kristjansson, & Agnew, 2012;Thornberry, Henry, Ireland, & Smith, 2010;Watts & McNulty, 2013).…”
Section: Gst and Victimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This third type of strain can include a wide range of stressful life events, such as criminal victimization or negative relationships with parents, teachers, or peers (Agnew & White, 1992). GST recognizes a number of victimization experiences that are likely to cause delinquency and have been neglected by other theories of crime (Agnew, 2002), and empirical tests of GST provide strong support for the victimization-delinquency relationship (Agnew, 1985(Agnew, , 2002Agnew & White, 1992;Jackson, Hanson, Amstadter, Saunders, & Kilpatrick, 2013;Mersky, Topitzes, & Reynolds, 2012;Moon, Morash, McCluskey, & Hwang, 2009;Sigfusdottir, Kristjansson, & Agnew, 2012;Thornberry, Henry, Ireland, & Smith, 2010;Watts & McNulty, 2013).…”
Section: Gst and Victimizationmentioning
confidence: 99%
“…Research testing the underlying role of negative affect in the victimization-delinquency relationship provides mixed support. Although some studies have found support for the full mediation GST model (Brezina, 1998;Carson, Sullivan, Cochran, & Lersch, 2009;Hay & Evans, 2006;Moon, Blurton, & McCluskey, 2008;Peck, 2013;Wallace, Patchin, & May, 2005;Watts & McNulty, 2013), others find that negative affect only partially mediates the relationship between victimization and delinquency (Brezina, 1998;Hay & Evans, 2006;Jang & Johnson, 2003).…”
Section: Gst and Victimizationmentioning
confidence: 99%
“…There is clear evidence that childhood abuse is related to an increased prevalence of mental health problems (e.g., [13]). Moreover, childhood abuse is a risk factor for later offending behavior [4]. Although childhood abuse is highly prevalent in juveniles who have sexually offended (JSOs) (e.g., [5]), little attention has been devoted to the direct relation between childhood abuse and mental health problems in this specific group of offenders.…”
Section: Introductionmentioning
confidence: 99%
“…And they add to what is known from mostly cross-sectional studies on patterns of antisocial behavior (e.g., Manly et al, 1994; Watts & McNulty, 2013). Of note in this study, the effect of parent-reported child abuse on adult crime was mediated by childhood antisocial behavior, whereas our measure of officially recorded child maltreatment predicted adult crime directly, suggesting that different sources of data on child abuse can relate to outcomes in a somewhat different manner.…”
Section: Discussionmentioning
confidence: 82%